EFEKTIVITAS DAN KARAKTERISTIK KOMBUCHA SARI BUAH STROBERI (Fragaria x ananassa)TERHADAP BAKTERI Streptococcus mutans DAN Basillus cereus SECARA IN VITRO - Sitorus, Widya Astuti; Rasyidah; Mayasari, Ulfayani (PendIPA Journal of Science Education, 2024)
Kombucha is a functional fermented drink using SCOBY. Kombucha with the addition of strawberry juice is the latest innovation that is expected to inhibit the growth of Streptococcus mutans and Bacillus cereus bacteria which are pathogenic bacteria that cause digestive disorders. The method used in this study was a disc diffusion test with a concentration of 20%, 30%, 40% and 50% fruit juice, where each treatment was repeated 3 times. The results of this study showed an average inhibition zone against Streptococcus mutans bacteria of 6.98mm, 8.38mm, 10.6mm, 6.5mm. While Bacillus cereus 6.46 mm, 7.5 mm, 9.18 mm and 5.85 mm. Based on the research results, it can be concluded that the inhibitory power of strawberry kombucha juice against Streptococus mutans bacteria is categorized as strong at a concentration of 40% with an inhibition zone of 10.61 mm while raisins are moderate on Bacillus cereus with the highest inhibition zone at a concentration of 40% of 9.18 mm. The characteristics of strawberry kombucha have a pH ranging from 3.21-3.55 with a distinctive fermented aroma, maroon red in color and have a sweet and sour taste. The alcohol content in strawberry kombucha juice is 0.01 which means this drink is halal for consumption. The viscosity of strawberry kombucha juice is 0.79 which means that strawberry kombucha juice has a low viscosity level.